Mengagas Konsep Moderasi Islam untuk Anak Usia Dini - A’la, Moh. Rofikil; shofwan, arif muzayin; Husnah, Ziadatul (Journal of Childhood Education, Development and Parenting, 2023)
Until now, the Islamic moderation term for early childhood is still very minimal. There are obstacles in explaining the terms of Islamic moderation in early childhood subjects, especially those who are still in the early stages of knowing the religion. Therefore, this paper tries to explore the concept of Islamic moderation for early childhood. This qualitative descriptive research uses a literature study in conducting its research. The data analysis technique uses content analysis by sorting out data according to the objectives and research problems. This paper produces several things as follows. First, Islamic moderation is a view or attitude that always tries to take a middle position from two opposing and excessive attitudes so that one of the two attitudes in question does not dominate in one's thoughts and attitudes. The basis is the hadith of the Prophet Muhammad "khairul umûr ausâthuha", meaning that the best problems are those in the middle. Second, Islamic moderation that can be implemented in early childhood has at least the following independent characteristics, including: (1) the existence of freedom rights that must be balanced with obligations; (2) there is a balance between worldly life and the hereafter, as well as material and spiritual. So that the civilization and progress achieved by Muslims are not a fictitious mirage, but essential and truly following what is expected, namely realizing goodness in the world and the hereafter and being kept away from the calamities and torments of hell